Comparison of 24 Hour Urinary Protein and Spot Urinary Protein- Creatinine Ratio in the Assessment of Proteinuria in Patients with Glomerulonephritis (Journal of Dhaka Medical College, 2015)
Context: Glomerulonephritis is an important cause of morbidity and mortality among all age group in Bangladesh. This cross sectional study was carried out with an aim to observe the comparison of 24 hour urinary protein and spot urinary protein- creatinine ratio in patients with glomerulonephritis in 3 group: on basis of 24 hour total protein, GFR level and serum albumin level.Methods: A total number of 128 consecutive patients having glomerulonephritis with 18 to 70 years who came in the Nephrology Unit, Dhaka Medical College Hospital, Dhaka, during the period of January to December of 2011 were included in this study. Patients with proteinuria other than glomerulonephritis like DM, UTI and Hypertension and